Synthesis, characterization and thermal behavior of 4-chloromethyl-2-(2-hydroxybenzilidenehydrazino) thiazole and its complexes with Cr(III), Co(II), Ni(II) and Cu(II) - Saydam, S; Yilmaz, E (Pergamon-Elsevier Science Ltd, 2006)
A new ligand, 4-chloromethyl-2-(2-hydroxybenzilidenehydrazino) thiazole, has been synthesized from dicholoroacetone and 2-hydroxybenzylidenethiosemicarbazon. Metal complexes of the ligand were prepared from acetate salts of Co(II), Cu(II), Ni(II) and chloride of Cr(III) in dry acetone. Characterization of the ligand and its complexes was made by microanalyses, FT-IR, C-13, H-1 NMR and UV-vis spectroscopy, magnetic susceptibility and thermogravimetric analysis. In the light of these results, it was suggested that two ligands coordinate to each metal atom by hydroxyl oxygen, imino nitrogen and thiazole ring nitrogen to form high spin octahedral complexes with Cr(III), Co(II), Ni(II) and Cu(II). (c) 2005 Elsevier B.V. All rights reserved.
Keywords: 4-chloromethylthiazole; 2-hydroxybenzilidenehydrazine; 4-chloromethyl-2-(2-hydroxybenzilidenehydrazino)thiazole; Cr(II), Co(II), Ni(II) and Cu(II); complex; synthesis